2006
DOI: 10.1007/s00125-006-0225-4
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid tyrosine phosphatase (LYP/PTPN22) Arg620Trp variant regulates insulin autoimmunity and progression to type 1 diabetes

Abstract: Aims/hypothesis: We analysed the contribution of the lymphoid protein tyrosine phosphatase (LYP) Arg620Trp variant (which corresponds to the PTPN22 C1858T polymorphism) to the emergence of beta-cellspecific humoral autoimmunity and progression to type 1 diabetes in man. We also explored the heterogeneity in the disease-predisposing effect of this polymorphism in relation to known disease loci, sex and age at disease onset. Subjects and methods: A population-derived Finnish birth cohort with increased disease s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
75
3
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 50 publications
14
75
3
1
Order By: Relevance
“…We have provided evidence of statistical interaction between HLA class II genotypes and a non-MHC HLA susceptibility locus in agreement with two previous studies from Hermann et al (29) and Steck et al (30). This interaction, which is less than multiplicative, cannot be interpreted biologically (42), and all that we are able to conclude from it is that despite the relative risk of PTPN22 being higher in low-risk HLA genotypes, the combined risk of diabetes for individuals carrying high-risk HLA and PTPN22 genotypes is higher than that for those carrying low risk HLA genotypes and high-risk PTPN22 genotypes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We have provided evidence of statistical interaction between HLA class II genotypes and a non-MHC HLA susceptibility locus in agreement with two previous studies from Hermann et al (29) and Steck et al (30). This interaction, which is less than multiplicative, cannot be interpreted biologically (42), and all that we are able to conclude from it is that despite the relative risk of PTPN22 being higher in low-risk HLA genotypes, the combined risk of diabetes for individuals carrying high-risk HLA and PTPN22 genotypes is higher than that for those carrying low risk HLA genotypes and high-risk PTPN22 genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…Hermann et al (29) observed that the effect of rs2476601/Trp 620 was more pronounced in subjects with non-DR4-DQ8/low-risk HLA genotypes (P ϭ 0.0004) from a dataset of 546 case subjects, 538 control subjects, and 245 nuclear families from Finland (mean age at diagnosis of case subjects 8.2 Ϯ 4.1 years). They also reported some evidence that boys carrying the rs2476601 Trp 620 allele were at higher risk of disease than girls (P ϭ 0.021; 29).…”
mentioning
confidence: 99%
“…Similar findings have been reported previously to extend to several autoimmune diseases (4,5) and on the appearance of insulin autoantibodies (IAA) in individuals positive for islet cell autoantibodies (ICAϩ) (23) and the risk of RF-positive rheumatoid arthritis (24). These observations support that the 1858T allele has a dose-dependant effect on the risk of several autoimmune diseases, including type 1 diabetes, consistent with the hypothesis that the underlying mechanisms may depend on a specific threshold (5).…”
Section: Discussionsupporting
confidence: 87%
“…This may be due to the inclusion criteria used, resulting in a relatively homogeneous study population, but may also reflect the idea that factors contributing to the initiation of the disease process might be different from those driving the process towards overt disease. However, as previously shown (2,3,6,21,22), several of the factors associated with the initiation of b-cell autoimmunity do contribute to the phenomena associated with the progression rate, such as age at initial seroconversion, the pace of progression towards persistent multipositivity and autoantibody levels. The current study confirmed the prior observations that progression to T1D is related to young age at seroconversion, early progression to multipositivity, higher numbers of detectable autoantibodies and to higher levels of ICA, IAA and IA-2A (1, 2, 3).…”
Section: Discussionmentioning
confidence: 81%